Antifibrotic Effect of a Novel Selective 11β-HSD2 Inhibitor (WZ51) in a rat Model of Myocardial Fibrosis - Zhuang, Fei; Ge, Qin; Qian, Jianchang; Wang, Zhe; Dong, Yaoyao; Chen, Mengchun; Zhang, Xiaodan; Sun, Wei (Frontiers in Pharmacology, 2021)
Myocardial fibrosis (MF) is one of the leading causes of end-stage heart disease. Many studies have confirmed that inflammation caused by aldosterone may play an important role in the process of MF. A selective 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) enzyme inhibitor can reduce the inactivation of cortisol, allowing cortisol to compete for mineralocorticoid receptors. This study investigated the protective effect of a novel selective 11βHSD2 inhibitor (WZ51) on MF and described its underlying mechanism. The administration of WZ51 in rats with MF significantly alleviated myocardial injury, accompanied by a decrease in lactate dehydrogenase and the creatine kinase myocardial band. Furthermore, WZ51 significantly inhibited the development of MF and increased the protein level of 11β-HSD2. The results of this study demonstrate that 11β-HSD2 plays an important pathological role in MF. Thus, WZ51 may be a potential therapeutic agent for the treatment of this condition.